ANALISIS FAKTOR YANG MEMPENGARUHI SUKU BUNGA KREDIT INVESTASI DI INDONESIA - Syahputra, Reisnanda Afkary; Santoso, Dwi Budi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to find out determinants of investment credit interest rates in Indonesia. This study uses a quantitative approach with the VAR analysis method. The data used in this study is secondary data in the form of a time series with quarterly time periods from Q1 2011 to Q4 2022. The study found that BI Rate increases investment credit interest rates. Then gross domestic product can increase investment credit interest rates, but will reduce investment credit interest rates in the longer period. The money supply has an indirect effect on investment credit interest rates through gross domestic product. These results recommend policies to maintain the BI Rate and the economy to remain stable so that it can provide convenience for business actors, the public and banks to encourage credit development.